The deceived : a new English translation of Gl'Ingannati in a dual-language edition - Beecher, Donald; Ciavolella, Massimo, 1942- (Italica Press Renaissance and modern plays series., 2018)
"The first modern English translation and dual-language edition of a Renaissance Italian comedy of intrigue, involving twins and mistaken identities, believed to be a source for Shakespeare's 'Twelfth Night.' Includes introduction, bibliography, plot summary, notes"--